nformation system for collecting and processing metrology data - Чака, А. А. (Problems of Informatization and Control, 2008)
Considered information system for collecting and processing metrology data, which consists of precision thermostat Lauda E200, personal computers and other software that allows data exchange using Channel Communications RS 232. The software package implemented by means of LabView applications